2022
DOI: 10.3390/children10010014
|View full text |Cite
|
Sign up to set email alerts
|

PRISM III Score Predicts Short-Term Outcome in Children with ARDS on Conventional and High-Frequency Oscillatory Ventilation

Abstract: Therapeutic recommendations for pediatric acute respiratory distress syndrome (PARDS) include conventional (CMV) and rescue high-frequency oscillatory mode (HFOV) of mechanical ventilation (MV). The pediatric risk of mortality (PRISM) is a frequently used mortality score for critically ill patients. In search of methods to recognize those patients, we analyzed the PRISM III score as a potential predictor of the short-term outcome in MV subjects with PARDS. A retrospective five-year study of PARDS in children o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Similarly, a study done in China that only recruited septic shock patients showed a much higher sAKI prevalence of 54.5% [ 27 ]. Patients with sepsis tend to have higher illness severity scores and are at a higher risk of AKI [ 32 ]. Differences in the age of the enrolled study participants could also explain the disparity in sAKI prevalence as younger age has been shown to correlate to an increased rate of developing sAKI [ 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study done in China that only recruited septic shock patients showed a much higher sAKI prevalence of 54.5% [ 27 ]. Patients with sepsis tend to have higher illness severity scores and are at a higher risk of AKI [ 32 ]. Differences in the age of the enrolled study participants could also explain the disparity in sAKI prevalence as younger age has been shown to correlate to an increased rate of developing sAKI [ 33 ]…”
Section: Discussionmentioning
confidence: 99%